Existence and asymptotic properties of solutions of a real system of differential equations unresolved with respect to the derivative - Prosenyuk, L. G. (Ukrains’kyi Matematychnyi Zhurnal, 1993)
A system of differential equations unresolved with respect to a derivative is studied. Sufficient conditions for the existence of solutions with singular initial data are found. The dimensionality of the set of these solutions is determined and their asymptotic properties are studied.